Postoperative In-Stent Thrombus Formation Following Frozen Elephant Trunk Total Arch Repair - Walter, Tim; Berger, Tim; Kondov, Stoyan; Gottardi, Roman; Benk, Julia; Rylski, Bartosz; Czerny, Martin; Kreibich, Maximilian (Frontiers in Cardiovascular Medicine, 2022)
Objectives Our aim was to investigate the occurrence and clinical consequence of postoperative in-stent thrombus formation following the frozen elephant trunk (FET) procedure. Methods Postoperative computed tomography angiography (CTA) scans of all 304 patients following the FET procedure between 04/2014 and 11/2021 were analysed retrospectively. Thrombus size and location were assessed in multiplanar reconstruction using IMPAX EE (Agfa HealthCare N.V., Morstel, Belgium) software. Patients’ characteristics and clinical outcomes were evaluated between patients with and without thrombus formation. Results During the study period, we detected a new postoperative in-stent thrombus in 19 patients (6%). These patients were significantly older (p = 0.009), predominantly female (p = 0.002) and were more commonly treated for aortic aneurysms (p = 0.001). In 15 patients (79%), the thrombi were located in the distal half of the FET stent-graft. Thrombus size was 18.9 mm (first quartile: 12.1; third quartile: 33.2). Distal embolisation occurred in 4 patients (21%) causing one in-hospital death caused by severe visceral ischaemia. Therapeutic anticoagulation was initiated in all patients. Overstenting with a conventional stent-graft placed within the FET stent-graft was the treatment in 2 patients (11%). Outcomes were comparable both groups. Female sex (p = 0.005; OR: 4.289) and an aortic aneurysm (p = 0.023; OR: 5.198) were identified as significant predictors for thrombus development. Conclusion Postoperative new thrombus formation within the FET stent-graft is a new, rare, but clinically highly relevant event. The embolisation of these thrombi can result in dismal postoperative outcomes. More research is therefore required to better identify patients at risk and improve perioperative treatment.